2019
DOI: 10.1016/j.semcdb.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights and therapeutic opportunities of antimicrobial chemokines

Abstract: Chemokines are a family of small proteins best known for their ability to orchestrate immune cell trafficking and recruitment to sites of infection. Their role in promoting host defense is multiplied by a number of additional receptor-dependent biological activities, and most, but not all, chemokines have been found to mediate direct antimicrobial effects against a broad range of microorganisms. The molecular mechanism(s) by which antimicrobial chemokines kill bacteria remains unknown; however, recent observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 111 publications
0
20
0
1
Order By: Relevance
“…Antimicrobial peptides (AMPs) are innate immune molecules that often exhibit a common antimicrobial mechanism of disrupting pathogen membranes, which leads to depolarization, leakage, and eventual cell death. , Examples of AMPs include cathelicidins, defensins, bacteriocins, histatins, protegrins, and, more recently, an increasing number of chemokines, which are more commonly thought of as signaling molecules. Among the human chemokines that exhibit antibacterial, antifungal, or antiviral properties are CCL20, CXCL4, CCL28, CXCL17, and XCL1 . Chemokines are a family of ∼50 small, secreted proteins that direct cellular migration by binding to glycosaminoglycans (GAGs) to form concentration gradients, and by binding to G-protein coupled receptors (GPCRs) to induce pro-migratory cellular changes.…”
mentioning
confidence: 99%
“…Antimicrobial peptides (AMPs) are innate immune molecules that often exhibit a common antimicrobial mechanism of disrupting pathogen membranes, which leads to depolarization, leakage, and eventual cell death. , Examples of AMPs include cathelicidins, defensins, bacteriocins, histatins, protegrins, and, more recently, an increasing number of chemokines, which are more commonly thought of as signaling molecules. Among the human chemokines that exhibit antibacterial, antifungal, or antiviral properties are CCL20, CXCL4, CCL28, CXCL17, and XCL1 . Chemokines are a family of ∼50 small, secreted proteins that direct cellular migration by binding to glycosaminoglycans (GAGs) to form concentration gradients, and by binding to G-protein coupled receptors (GPCRs) to induce pro-migratory cellular changes.…”
mentioning
confidence: 99%
“…In the genital mucosa, significant reductions of chemokines MIP‐3α and MCP‐1 were observed in Exposed. Chemokines are critical in combating infection by their participation in the inflammatory process 46,47 . MIP‐3α chemo‐attracts T cells and has in vitro HIV inhibitory activity 48‐50 .…”
Section: Discussionmentioning
confidence: 99%
“…It is becoming increasingly recognized that chemokines have functions beyond the direction of cell migration, and one such function is direct antimicrobial activity against invading pathogens. Indeed, the immunologic functions of both chemokines and antimicrobial peptides (AMPs) have considerable overlap, with members of each family acting as both chemoattractants and antimicrobial agents [2527]. The physiologic significance of the antimicrobial functions of chemokines remains unclear, but it has been proposed that they may allow for a more robust immunologic response to microbial infection in vivo [27].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the immunologic functions of both chemokines and antimicrobial peptides (AMPs) have considerable overlap, with members of each family acting as both chemoattractants and antimicrobial agents [2527]. The physiologic significance of the antimicrobial functions of chemokines remains unclear, but it has been proposed that they may allow for a more robust immunologic response to microbial infection in vivo [27]. Additionally, it has been suggested that the antimicrobial activities of homeostatic chemokines may be important for controlling commensal microbial populations [5].…”
Section: Discussionmentioning
confidence: 99%